ANALYSIS OF FINANCIAL PERFORMANCE OF BPD DIY AND BANK BJB FOR THE 2017-2022 - Aprilia, Angeline; Paramitalaksmi, Ratri (Universitas Methodist Indonesia, 2024)
This research aims to determine the comparison of financial performance between BPD DIY and Bank BJB (formerly: BPD Jabar) in the 2019-2022 period. This study used quantitative methods. Quantitative methods are applied to analyze financial ratios where data are presented in numerical form. From the results of the ROA calculation, it is known that BPD DIY banks operate much more efficiently than BPD BJB bank’s because the ROA value obtained is greater so that the bank's ability to generate profits is better. From the LDR calculation, it is known that BJB BPD bank has sufficient liquidity but may have lower income, while DIY BPD does not have enough liquidity to cover customer obligation. From the results of the CAR calculation, it can be seen that both banks have good financial system stability against possible risk of loss, with a minimum guarantee limit of 8%. This research is expected to be a reference for consideration to analyze the comparison of BPD DIY and Bank BJB and other banks in the future.